The consequences of indiscriminate use of Ritalin by university students in the health area in Brazil (Research, Society and Development, 2022)
Methylphenidate (MPH) was first synthesized in 1944, already in 1955 the pharmaceutical company Ciba-Geigy (precursor to Novartis) was responsible for launching the product on the market. It is a psychotropic drug commonly used by people with attention deficit disorder. and hyperactivity (ADHD) and narcolepsy, which acts as a central nervous system stimulant, being part of the amphetamine family. When the drug is used improperly, it may have reactions. Therefore, this research aimed to explain and analyze the effectiveness and safety in the use of Ritalin® by university students in the health area in Brazil, which are the effects that this medication can cause in the human body. A comprehensive literature review was carried out and the articles in this review were collected from the following electronic research databases: MEDLINE/PUBMED, LILACS and SCIELO, between 2013 and 2022. 80 articles were identified, 20 of which were used in the elaboration of the work . The results of this research can lead to reflection for students showing damages that the indiscriminate use of psychostimulants, especially Ritalin®, can harm the user who self-medicates. The indiscriminate use causes neurological, physical and mental consequences in the people who consume it, making us think about the intake and sale of this medication to audiences such as university students, and that the prescription and correct medical follow-up are indispensable.